Potential Combination of Xanthone Compounds from Mangosteen Fruit (Garcinia mangostana) with Eugenol Compounds in Basic Leaf (Ocimum sanctum) as Alternative Therapy in Preeclampsia - Muhammad Al Farisi Sutrisno (HM Publisher, 2021)
Preeclampsia is a hyperdynamic condition that is syndromed by hypertension and proteinuria after 20 weeks of pregnancy. Preeclampsia incident is the first cause of 6- 8 % number morbidity/mortality maternity and fetus in the world. Preeclampsia is related to the disability of physiology adaptation that can decrease perfusion of uteroplacental. Xanthone derivatives in mangosteen have been reported to possess a wide range of biological properties, including antioxidant and antihypertensive activities. Eugenol is a primary component of basil oil. It is known for its antioxidant, antiinflammatory, and vasorelaxant actions. These beneficial effects of eugenol make it an excellent therapeutic candidate for the treatment of hypertensive disorders of pregnancy. This study wants to analyze the best available research evidence on the potential combination of xanthone compounds from mangosteen fruit (Garcinia mangostana) with eugenol compounds in basil leaf (Ocimum sanctum) as an alternative therapy in preeclampsia. A literature review was conducted in the electronic databases PubMed and Google Scholar using the index terms